Tefl student teachers’ awareness and application of achievement standards in English language teaching = Nhận thức và áp dụng các chuẩn đầu ra trong giảng dạy ngoại ngữ của sinh viên năm 3 khoa sư phạm tiếng Anh, Đại học Ngoại ngữ - Trần, Thị Vân Anh (2020)
The research was carried out in Vietnam where the Common European Framework of Reference for Languages (CEFR) and achievement requirements stated in Dispatch 5333 have been set as two of the official standards in the language education sector. Despite the significance of two mentioned sets of standards, there has been a serious lack of studies about these sets, especially about the awareness and alignments of pre-service teachers, who will play an important role in the standards adoption in the future. With a view to bridging this gap, the current paper aims to shed light on TEFL students teachers’ awareness and application of achievement standards in English Language Teaching, based on stages of teaching practice created by combining the features of standard-based teaching created by Biggs (2003), teaching domains devised Danielson (1996) and examples proposed by UCLES (2011). Via the questionnaire and interviews, the study has found that pre-service teachers at this language university in Hanoi were at the moderate awareness with CEFR-V and were somewhat aware of achievement standards stated in Dispatch 5333, yet aligned them at significantly different levels in their teaching practice. Furthermore, they expressed varied challenges in standards aligning, such as lack of experiences and feedback. In light of these findings, the study recommends that pre-service teachers should proactively learn more about CEFR-V and Dispatch 5333 and that two sets of standards should be mentioned and emphasized more in the textbooks and lecturers’ feedback. Additionally, attempts should be made by standards developers to make the framework more accessible to its end-users, namely teachers and learners